The impact of 3D printed vs. 3D virtual congenital heart models on patient and family knowledge - Zerwic, Luke; Mohan, Ashray; Riley, Emily; Byeman, Connor; Ashwath, Ravi (Frontiers in Pediatrics, 2025)
IntroductionCongenital heart defects (CHDs) often involve complex anatomical structures that can be challenging for patients and their families to understand. While physicians utilize various imaging techniques such as cardiac echocardiograms, CT scans, and MRIs to comprehend these complexities, the information is typically conveyed to patients and families through two-dimensional (2D) images and drawings. Traditional methods often fail to fully capture the intricate nature of CHDs. This study compared the effectiveness of 2D imaging with three-dimensional (3D) virtual and 3D printed models in enhancing the understanding of CHDs among patients and their families.MethodsFamily members of patients with congenital heart disease, as well as patients aged 15 years or older, were recruited for the study. Participants were presented with an echocardiogram of their specific cardiac defect alongside an echocardiogram of a structurally normal heart for comparison. They were then randomly assigned to receive education using a 3D printed model or a 3D virtual model of their heart defect. Participants' knowledge of normal cardiac anatomy and the anatomy of their specific cardiac defect was assessed after viewing the echocardiogram (2D image) and again after reviewing the 3D models.ResultsOne-hundred-nine subjects participated in the study, comprising 79 family members (72.5%) and 30 patients (27.5%). Subjects showed significant improvement in their understanding of normal cardiac anatomy with both 3D printed and 3D virtual models compared to the 2D image (p = 0.022 and p = 0.012, respectively). Among the subjects, 70% in the 3D printed group and 84% in the 3D virtual group indicated a preference for the 3D models over the 2D image. Both the 3D printed, and 3D virtual model groups rated themselves as having an increased understanding of normal cardiac anatomy compared to the 2D images (p = 0.009 and p < 0.001, respectively).DiscussionThese findings suggest that incorporating 3D models into the educational process for patients with congenital heart disease can lead to improved comprehension and greater satisfaction.